Foucault on Discourse: O'Neill as Discourse: LDJN (4: 125 - 154) Tyrone and Edmund - Proehl, Geoffrey S. (Journal of Dramatic Theory and Criticism, 1990)
Foucault on Discourse: O'Neill as Discourse: LDJN (4: 125 - 154) Tyrone and Edmund